Continuing Professional Development of College Teachers in Higher Education - Singh, Chandra B.P. (JOURNAL OF INDIAN EDUCATION, 2017)
Three hundred and thirty-five teachers working in three state-affiliated universities for the past 10 years were randomly selected for the study. Two self-reporting measures — Continuing Professional Development (CPD) and change in learning — were employed for data collection. Factor analysis yielded four dimensions of CPD — internal, external, research and collaborative. Besides, the CPD had two facets — belief and practice. The analysis also highlighted that teachers had less collaborative orientation and more internal orientation. Ideally, teachers had strong beliefs in CPD. But in practice, they did not show it. Professional learning practices did not alter belief values but had brought a change in teaching practices.